2006
DOI: 10.1007/s00424-006-0173-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of hEAG1 potassium channels by arachidonic acid

Abstract: The depolarisation activated human ether à go-go (hEAG) potassium channels are primarily expressed in neuronal tissue but their appearance in various tumour entities is also indicative of an oncogenic role. Because upregulation of hEAG channels may yield to an enhanced cell proliferation, interventions increasing hEAG1 currents may serve similar purposes. We therefore investigated the effects of polyunsaturated fatty acids on hEAG1 channels. Arachidonic acid (AA) lowered their activation threshold, accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…Eag1 channel activity is increased by arachidonic acid in IGR1 melanoma cells (46), and insulin-like growth factor-I increases both channel activity and gene expression of Eag1 in MCF-7 breast cancer cells (47). Here, we show for the first time Eag regulation by cancer risk factors in normal cells.…”
Section: Discussionmentioning
confidence: 53%
“…Eag1 channel activity is increased by arachidonic acid in IGR1 melanoma cells (46), and insulin-like growth factor-I increases both channel activity and gene expression of Eag1 in MCF-7 breast cancer cells (47). Here, we show for the first time Eag regulation by cancer risk factors in normal cells.…”
Section: Discussionmentioning
confidence: 53%
“…Open-channel blockage by polyunsaturated FFA, apparently by binding of the FFA to an external site in the channel, was also reported for the major voltage-dependent K + channel (Kv1.5) cloned from cardiac cells (Honoré et al, 1994; Guizy et al, 2008). In contrast to this effect, Gavrilova-Ruch et al (2007) reported that AA activated human ether à go-go (hEAG) potassium channels expressed in CHO cells, an effect totally reversed upon washing with BSA. The potentiation effect was directly dependent on the number of cis -double bonds in the FFA, and probably involved a direct mechanism of action, as ETYA also potentiated hEAG currents, presumably acting through the outer membrane leaflet.…”
Section: Ffa Effects On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…The fact that FFA activate hEAG channels whereas they inactivate HERG channels may be due to structural differences in the pore mouth which, in the case of hEAG channels, would prevent the access of AA to the permeation pathway. These channels are normally expressed in neuronal tissue but also in various tumoral tissues, pointing to a possible oncogenic role; the activating effect of AA on EAG channels has therefore been related to an enhanced tumor proliferative rate (Gavrilova-Ruch et al, 2007). …”
Section: Ffa Effects On Voltage-gated Ion Channelsmentioning
confidence: 99%
“…b, (Béhé et al, 1992; Villarroel, 1993, 1994; Yu, 1995; Doolan et al, 2002; Milberg et al, 2011; Liin et al, 2015, 2016a,b; Moreno et al, 2015). c, (Schledermann et al, 2001; Liu and Wu, 2003; Wang et al, 2004; Guizy et al, 2005; Gavrilova-Ruch et al, 2007). d, (Bregestovski et al, 1989; Kirber et al, 1992; Ling et al, 1992; Ahn et al, 1994; Duerson et al, 1996; Zou et al, 1996; Twitchell et al, 1997; Devor and Frizzell, 1998; Stockand et al, 1998; Denson et al, 1999, 2000, 2005, 2006; Barlow et al, 2000; Wu et al, 2000; Fukao et al, 2001; Lu et al, 2001, 2005; Zhang et al, 2001; Zhang P. et al, 2008; Clarke et al, 2002, 2003; Lauterbach et al, 2002; Li et al, 2002, 2010; Ye et al, 2002; Hamilton et al, 2003; Gauthier et al, 2004, 2014; Zheng et al, 2005, 2008; Yang M. et al, 2005; Sun et al, 2007, 2009; Morin et al, 2007a,b,c; Gebremedhin et al, 2008; Godlewski et al, 2009; Lai et al, 2009; Wang et al, 2011a,b; Enyeart and Enyeart, 2013; Harris et al, 2013; Latorre and Contreras, 2013; Hoshi et al, 2013a,b,c,d; Kacik et al, 2014; Martín et al, 2014; Olszewska et al, 2014; Yan et al, 2014).…”
Section: Effects Of Pufa On Voltage-gated Ion Channelsmentioning
confidence: 99%